A Relação entre desempenho social e desempenho econômico: um estudo no setor de consumo não cíclico por meio da DVA - Brugnera, Tiago Luis (2017)
Financial performance indicators are the most sought-after diagnostic methods by enterprise’s stakeholders, such as profitability, payable capacity and capital management. However, a growing interest has been redirected to the social reflexes of business activities, beyond the economic result. One of the contemporary ways of evaluating social indicators is by analyzing quotients from the Value Added Statement (VAS), an accounting statement integrated to Brazilian accounting by Law 11,638 / 2007. After selecting economic and social performance variables, the present paper aimed to investigate the possible correlation between such constructs in the non-cyclical market segment of the Brazilian stock market. Data collected by analyzing the individual financial statements of the entities selected revealed a strong canonical correlation between social performance and economic performance, with highlights to the correlated power between profitability, indebtedness and the potential of the entity's net equity to generate added value.